2009
DOI: 10.3133/ofr20091046
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Selected Pharmaceutical and Organic Wastewater Compounds in Effluent and Water Samples from Municipal Wastewater and Drinking-Water Treatment Facilities in the Tar and Cape Fear River Basins, North Carolina, 2003-2005

Abstract: Multiply By To obtain mile (mi) 1.609 kilometer (km) square mile (mi 2) 2.590 square kilometer (km 2) million gallons per day (Mgal/d) 0.04381 cubic meter per second (m 3 /s) Horizontal coordinate information is referenced to the North American Datum of 1983 (NAD 83). Concentrations of chemical constituents in water are given in micrograms per liter (μg/L) unless otherwise noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The Cape Fear River basin is the largest river basin in North Carolina and has an area of approximately 9,183 mi 2 . The basin is highly developed in its headwaters where the most populated cities are located (Ferrell, 2009). The Cape Fear River is 200 mi long and flows southeast into the Atlantic Ocean (Ferrell, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cape Fear River basin is the largest river basin in North Carolina and has an area of approximately 9,183 mi 2 . The basin is highly developed in its headwaters where the most populated cities are located (Ferrell, 2009). The Cape Fear River is 200 mi long and flows southeast into the Atlantic Ocean (Ferrell, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The basin is highly developed in its headwaters where the most populated cities are located (Ferrell, 2009). The Cape Fear River is 200 mi long and flows southeast into the Atlantic Ocean (Ferrell, 2009). The river provides drinking water to residents in the basin area, and some of the intakes are located downstream of WWTPs, which can be affected by WWTP effluent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum concentrations of tributyl phosphate, tris(2-butoxyethyl)phosphate, and tris(dichloroisopropyl)phosphate in untreated-influent samples were 0.99, 51.0, and 1.3 µg/L, respectively (Null and others, 2019). BPA, a common plasticizer (Ferrell, 2009), was detected in 93 percent of untreated-influent samples but was not detected in treated-effluent samples. Maximum concentrations of BPA were 1.01 and less than 0.20 µg/L (less than the LRL), in untreated-influent and treated-effluent samples, respectively (Null and others, 2019).…”
Section: Flame Retardants and Plasticizersmentioning
confidence: 98%
“…Buxton and Kolpin (2002) reported that several compounds, steroids, insect repellents, and nonprescription drugs were frequently detected in surface-water samples collected across the United States. Examples of recent reports documenting the presence of CECs in the aquatic environment in different parts of the United States include reports pertaining to the presence of CECs in North Carolina (Ferrell, 2009); Minnesota (Lee and others, 2010); Pennsylvania (Reif and others, 2012); and Wisconsin (Tomasek and others, 2012). Opsahl and Lambert (2013) also reported on the presence of CECs in the San Antonio River Basin in south-central Texas, and evaluated detections, concentrations, and distribution patterns of selected CECs downstream from effluent discharge locations in San Antonio.…”
Section: Introductionmentioning
confidence: 99%